Application of a test to measure the attitude of the local population towards a health center in the city of S. Paulo (Brazil) - L'Abbate, Solange; Westphal, Márcia Faria (Revista de Saúde Pública, 1979)
A survey of the attitude towards a health center was made among a sample of inhabitants of two districts of S. Paulo city (Brazil). Indirect Questioning was carried out using an attitude scale created after Thurstone & Chave. Reliability tests made it possible to reduce the original scale from 55 to 24 items which can eventually be utilized in further surveys. The statements of the scale comprised 4 areas considered to be basic for the conceptual definition of attitudes regarding a health center: relationship between physician and patient; relationship between non-medical staff and patient; efficiency of services provided; and the physical and social milieu.